Dewan Komisaris dan Biaya Utang - Citra Sarasmitha; Bambang Subroto; Aulia Fuad Rahman (Jurnal Ekonomi Modernisasi, 2018)
This study examine the effect of board stock ownership, board size, frequency of board meeting, and the independence of the board against the cost of debt (bonds). The population in this study is a bond that has a yield to maturity (t + 1) number in the period 2012-2016. The sample method used is purposive sampling. Methods of data analysis using multiple regression. The results of this research indicate that board stock ownership, board size, the frequency of meetings of the board, and the independence of the board does not affect the cost of debt (bond). The results of the first and second sensitivity test show that board stock ownership, board size, the frequency of meetings of the board, and the independence of the board do not affect the bond rating. The research finding show that the board of commissioners has not been able to contribute to the reduction in bond debt costs. The results of this study are in line with the phenomenon in Indonesia that there are only 4 public companies that entered the ASEAN 50 TOP award of the Asean Corporate Gorvenance Scorecard in 2017. These conditions illustrate that corporate governance in Indonesia is still weak.The results of this study are not able to support agency theory and theory of the firm. The results of this study can be used by OJK to improve the standards of the board.